An Analysis of Expressive Speech Acts in Podcast: Joe Rogan Experience - I Made TirtaYasa; Putu Gede Budiartha (Universitas Islam Negeri Palopo, 2026)
In spoken communication, expressive speech acts such as praise play a crucial role in reflecting the speaker's psychological state and shaping social interaction. While many studies have explored speech acts in scripted media like films or talk shows, few have investigated how praise is naturally expressed in unscripted, long-form podcast discourse. This study aims to fill that gap by analyzing praising expressive speech acts in the podcast episode Joe Rogan Experience #2275, featuring Joe Rogan and the World Chess Champion, Magnus Carlsen. The analysis is grounded in Searle’s (1979) speech act theory, focusing on identifying the forms and pragmatic functions of praise. Using a qualitative descriptive method with purposive sampling, ten praising utterances were extracted and analyzed in context. The findings reveal that praise in this podcast is predominantly delivered implicitly, using informal and emotionally charged language. Pragmatically, both Rogan and Carlsen use praise not only to acknowledge intelligence and talent but also to build interpersonal rapport, validate expertise, and align shared values. These results highlight that in spontaneous digital conversation, praise functions as a strategic tool for maintaining social dynamics rather than merely offering compliments.